Eficiência de biodigestores canadenses no tratamento de dejetos de suínos em diferentes fases de produção - Andrade, Michelle Pellizer de (2018)
A swine breeding is an activity of great importance for the economy of the country, however, it is also recognized as having great polluting potential, due to the generation of large quantities of effluents with emission of organic matter load. Untreated waste strewn in the soil and water sources can cause environmental imbalances. To minimize the impact caused by wastes, the use of treatment systems, as the biodigester, is needed. The objective of this study is to evaluate the efficiency of canadian biodigesters in the reduction of pollutant loads from pig manure, through the analysis of physical-chemical parameters. The analyzes were carried out in the affluent and effluent of the biodigesters from three sites of different breeding stages (Site 1 - Reproduction and maternity; Site 2 - Nursery; Site 3 - Growth and termination). In order to analyze the efficiency of the reduction of pollutants of the manure, the following physico-chemical parameters were analyzed at the entrance and exit of the biodigesters: Chemical oxygen demand (COD), Total solids (ST), Fixed solids (SF), Volatile solids (SV), total Nitrogen, total phosphorus and pH. With the results found, it was possible to verify that the anaerobic treatment system was different in the three sites. Production site 1 was the one with the highest reductions: 17.12%; 25.77%; 64.18%; 67.48%; 48.20% and 78.07%, respectively for COD, Nitrogen, Phosphorus, ST, SF and SV. With the results obtained it was possible to verify that the anaerobic treatment system was efficient to reduce and stabilize the organic matter of the swine supply in all the sites, but it is not enough for the effluent to pour into water bodies. The effluent has potential to be used as a biofertilizer.